Future Electricity Demand in Asia: Policy Scenarios Using BAU Analysis - Tachrir Tachrir; Hasddin Hasddin; Muhamad Idham Handa; Haydir Haydir; Villa Evadelvia Ginal Sambari; Jasman Jasman; Eva Safitri Maladeni; Osu Oheputra Husen; Alfian Ishak; Asrul Asrul (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
Electricity demand in Asia has grown substantially over the past three decades, creating a persistent imbalance between supply and consumption. This study analyzes long-term trends in the electricity supply–demand gap from 1993 to 2022 and develops forecasting models to support energy management and policy planning through 2052. Using quantitative time series methods, two scenarios are generated: Business as Usual (BAU) and Additional Efforts. The analysis shows that electricity demand will continue to rise across both scenarios, driven by industrial expansion and rapid urbanization. Although policy interventions and technological improvements help moderate growth, they are not sufficient to fully offset future demand pressures. The study underscores the importance of accelerating renewable energy deployment, improving energy efficiency, and strengthening transmission infrastructure. A short-term increase in efficiency-oriented efforts is essential for stabilizing the regional energy system. The findings provide actionable insights for policymakers and energy managers, offering an evidence-based foundation for designing sustainable electricity strategies that address Asia’s growing energy needs.